The global burden of tuberculosis attributable to diet high in processed meat from 1990 to 2021: findings from the Global Burden of Disease Study 2021 - Wang, Linlin; Wang, Honglu; Wang, Yifei; Ma, Chao; Shi, Xinying (Frontiers in Nutrition, 2026)
BackgroundProcessed meats can increase the risk of tuberculosis (TB) infection by inducing chronic inflammation, disrupting the balance of the gut microbiota, and impairing metabolic health through their content of saturated fats, salt, and various additives. This study aims to analyze the global trends in the burden of TB attributable to diets high in processed meat (DHPM) from 1990 to 2021, and to explore the impacts of sex, age, and sociodemographic index (SDI) on these trends.MethodsData were obtained from the global burden of disease study 2021 (GBD 2021). The DisMod-MR 2.1 model was used to integrate global data, focusing on two key indicators: disability-adjusted life years (DALYs) and mortality.ResultsIn 2021, the global number of DALYs due to TB attributable to DHPM was 78,891.94, and the number of deaths was 2,361.79, representing decreases of 4 and 8%, respectively, compared to 1990. The highest DALYs and death cases were observed in low-middle SDI regions, while the fastest increases occurred in low SDI regions. The age group with the highest DALYs cases for both males and females was 50–54 years, while the highest number of deaths occurred in the 55–59 age group, with males bearing a significantly higher burden than females. Approximately 47% of countries experienced an upward trend in DALYs and 43% in death cases. Countries with lower SDI levels bear a heavier TB burden, and the inequality has not shown significant improvement.ConclusionAlthough the global burden of TB attributable to DHPM has shown an overall declining trend, marked regional disparities persist, with low SDI regions and males facing higher risks.